Impact of animal manure EM-bokashi on seed yield and quality of vegetable cowpea (Vigna unguiculata L.) (Bangladesh Journal of Scientific and Industrial Research, 2013)
The study was undertaken to investigate the effect of EM treated animal manures (named as animal manure EM-bokashi) on yield and nutritional composition of seeds of vegetable cowpea (Vigna unguiculata L.). This experiment was carried out with five treatments and 15 replications. The pots were arranged in a completely randomized way in the net house. The treatments included a non-fertilizer application as a control, the recommended chemical fertilizer dose and three types of animal manure EM-bokashi (cattle manure EM-bokashi, goat manure EM-bokashi and poultry manure EM-bokashi). The results showed that application of EM treated animal manures significantly increased the number of leaves caused greater nodulation, produced higher number of pods per plant, yielded maximum number of seeds per pod, greater 100 seed weight, higher yield and increased seed quality compared to chemical and non-fertilizer treatments. Among the different types of animal manure EM-bokashi, goat manure EM-bokashi applied plants produced comparatively higher seed yield with good nutritional value in the present study thus it is most suitable for obtaining higher economic yield and better seed quality of vegetable cowpea on sandy regosol. DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15411 Bangladesh J. Sci. Ind. Res. 48(1), 33-38, 2013